Major and minor perineural invasion in salivary gland cancer - Liu, Fei; Chu, Yinglin; Zheng, Qizhe; Hu, Yunshuang; Wang, Yiyi; Qin, Lu; Fu, Shuaikun; Wang, Suping (Frontiers in Oncology, 2025)
ObjectiveTo delineate the distribution of perineural invasion (PNI), evaluate its impact on patient survival, and identify optimal criteria for initiating adjuvant radiation therapy (RT) in cases of PNI associated with salivary gland cancer (SGC).MethodsThis retrospective study categorized enrolled patients into three groups based on PNI status (none, minor, or major), defined by the extent of nerve involvement. The influence of PNI on overall survival and locoregional control was assessed using a Cox proportional hazards model.ResultsA total of 555 patients were incorporated into the study. Logistic regression analysis indicated that tumor stage, neck stage, histological grade, and pathological type were independently linked to the occurrence of PNI. In the Cox model assessing overall survival, patients exhibiting minor nerve PNI demonstrated a hazard ratio (HR) of 1.78 [95% CI: 1.14-2.47] in comparison to those without PNI, a difference that was statistically significant (p<0.001). Conversely, the variation in HR between patients with major nerve PNI and those with minor nerve PNI was not statistically significant (p=0.673). In the Cox model for locoregional control, patients with minor and major nerve PNI exhibited HRs of 1.64 [95% CI: 1.17-2.78] and 1.65 [95% CI: 1.03-2.90], respectively, when compared to those without PNI. Subgroup analyses revealed that the incorporation of chemotherapy into radiotherapy did not significantly modify the risk of mortality or locoregional recurrence in comparison to patients treated with radiotherapy alone, irrespective of PNI classification.ConclusionBoth minor and major nerve PNI exerting comparable influences on prognosis, the adjunctive use of chemotherapy in combination with RT did not yield improvements in overall survival or locoregional control, irrespective of PNI status.